DAMPAK SEMA NOMOR 1 TAHUN 2022 TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NO. 23/PUU-XIX/2021 DALAM UPAYA HUKUM KASASI TERHADAP PUTUSAN PKPU - Jufriyadi, Jufriyadi; Purba, Jan Thetuko Syah Putra (Cattleya Darmaya Fortuna, 2025)
The Constitutional Court's Decision No. 23/PUU-XIX/2021, which opens the door for cassation appeals against PKPU decisions, does not provide any benefits to either creditors or debtors in terms of quickly resolving debt obligations. This creates uncertainty for creditors regarding their claims against debtors, especially since, following the Constitutional Court's decision, the legal procedures for cassation remain unclear, and if cassation is granted, creditors will not have clarity on the resolution of their debts. Following the issuance of SEMA No. 1 of 2022, which reinstates the legal norm that PKPU decisions cannot be subject to cassation appeals as per Article 235(1), this provides legal certainty. However, on the other hand, the status of SEMA No. 1 of 2022, which is not part of the legislation, may lead to multiple interpretations among creditors regarding which rules should be applied in implementing the legal provisions of PKPU decisions. The purpose of a PKPU application, whether by the debtor or creditor, is to restructure debts. A PKPU application is not exclusively the domain of the debtor; creditors are also granted the same opportunity to file a PKPU application against the debtor, as stipulated in Article 222(3) of the UUK-PKPU. The PKPU ruling, as stipulated in Article 235(1), is not subject to cassation, as the PKPU proceedings are swift and simple. The granting of a PKPU application benefits both the debtor and the creditor by enabling them to settle their debts through a peace proposal submitted by the debtor